2017
DOI: 10.1186/s12864-017-3821-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of additive, dominance, and imprinting effects for production and reproduction traits in Holstein cattle

Abstract: BackgroundAlthough genome-wide association and genomic selection studies have primarily focused on additive effects, dominance and imprinting effects play an important role in mammalian biology and development. The degree to which these non-additive genetic effects contribute to phenotypic variation and whether QTL acting in a non-additive manner can be detected in genetic association studies remain controversial.ResultsTo empirically answer these questions, we analyzed a large cattle dataset that consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 36 publications
11
41
0
Order By: Relevance
“…where y is a phenotype vector of size n for a complex trait, b is a vector of covariate (other than genomic variants) effects and X is corresponding design matrix, a is a vector of variant effects and Z is corresponding genotype coding matrix (e.g., genotype coding for additive, dominance, or imprinting effects 34 ), g is a vector of polygenic effect for controlling population structure, G is a corresponding variance structure matrix (e.g., genomic relationship matrix), and e is the residual with variance structure R for modelling reliability or accuracy of phenotypic records as in model (1) We seek to identify independent association signals within a QTL region and to assign a posterior probability of causality (PPC) to each variant with fine-mapping. Following the method by Huang et al 7 , our fine-mapping approach includes three steps: forward selection 37 to add independent signals in the model, repositioning signals, and generating credible variant set for each signal.…”
Section: Bayesian Fine-mapping (Bfmap)mentioning
confidence: 99%
“…where y is a phenotype vector of size n for a complex trait, b is a vector of covariate (other than genomic variants) effects and X is corresponding design matrix, a is a vector of variant effects and Z is corresponding genotype coding matrix (e.g., genotype coding for additive, dominance, or imprinting effects 34 ), g is a vector of polygenic effect for controlling population structure, G is a corresponding variance structure matrix (e.g., genomic relationship matrix), and e is the residual with variance structure R for modelling reliability or accuracy of phenotypic records as in model (1) We seek to identify independent association signals within a QTL region and to assign a posterior probability of causality (PPC) to each variant with fine-mapping. Following the method by Huang et al 7 , our fine-mapping approach includes three steps: forward selection 37 to add independent signals in the model, repositioning signals, and generating credible variant set for each signal.…”
Section: Bayesian Fine-mapping (Bfmap)mentioning
confidence: 99%
“…However, buffalo milk yield was known to be much lower than that of cow [2], which largely restricts the development of the dairy buffalo industry. The milk traits are complex quantitative traits with moderate heritability [3][4][5]. With the application of genome-wide association studies for mapping genes for complex traits in domestic animals, several necessary genes related to lactation phenotypes have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, rs109376747 in LDLR also significantly associated with CHL_milk based on a dominance effect, although this effect (dominance effect) explained only a smaller proportion (0.41%) of the total phenotypic variance in CHL_milk compared with variance explained by the additive effect (2.47%) of this SNP (Table ). It has been reported that phenotypic variance explained by a dominance effect was much lower than that explained by an additive effect for milk traits in dairy cows (Ertl et al ; Aliloo et al ; Jiang et al ; Varona et al ). Moreover, SNPs in three other genes (rs137347384 in RBM19 , rs42016945 in PPARG and rs110862179 in SCAP) were also significantly associated with CHL_milk based on a dominance effect .…”
Section: Discussionmentioning
confidence: 98%